Guidelines for Using Simulation for Online Teaching and Learning of Clinical Social Work Practice in the Time of COVID - Bay, Uschi (Clin Soc Work J, 2021)
Due to COVID 19, Monash University’s Social Work Department moved all clinical practice skills teaching in the Master of Social Work (graduate entry level) fully online using synchronous audio-visual conferencing platform Zoom for the first time from March to June 2020. The innovations associated with this move included the development of clinical practice laboratories (CPLs) to prepare 154 students for a modified version of an Objective Structured Clinical Examinations (OSCE) and their first field education practicum. The use of simulated clients to facilitate experiential learning of active listening skills, rapport-building and empathic communication in this mode of delivery is described in detail to encourage overcoming previous issues in teaching clinical practice skills to students located at a distance from campus.